Systems integration in infrastructure projects: seven lessons from Crossrail. (January 2022) - Whyte, Jennifer; Davies, Andrew; Sexton, Chris
Abstract : A systems integration model for the delivery of complex infrastructure projects is proposed. From the Crossrail case, the authors draw seven lessons for clients to: (1) manage programme delivery as an integration activity; (2) actively manage systems integration; (3) ensure authority to make decisions; (4) maintain configuration control; (5) plan for a lengthy testing and commissioning phase; (6) appreciate supply chain products that may be part of unaligned global research and development programmes; and (7) do final integration only when there is something to integrate. Central to the argument is the idea that on such complex projects, the client cannot outsource systems integration and thus needs to recognise they retain accountability, though roles and responsibilities can be assigned to the delivery partner, supply chain, chief engineer and/or contracted systems integration firm. A key question for the client at the outset is how to distribute interface management and systems integration responsibilities while retaining accountability and oversight. Rather than managing through contracts, budgets and schedules, the authors suggest a changed approach with priority given to managing integration, and contracts, budgets and schedules that support and incentivise this.